Dam Construction, Company Towns and Planned Urban Development: The Example of Salto del Esla, Spain. - Plasencia-Lozano, Pedro; Bargón-García, Marina (Industrial Archaeology Review, 2024)
Company towns are integral to the urban and territorial changes wrought by the Industrial Revolution, especially in remote, resource-rich areas. Among these, villages constructed alongside dams stand out due to their profound territorial impact. This study focuses on one such unique settlement near the Ricobayo dam in Zamora, Spain, exploring its construction and environmental integration. At its inception, Ricobayo was Europe's largest dam, its creation marked by notable feats like relocating a church, and pioneering hydraulic engineering and bridge construction, including a record-breaking design by Torroja. The adjacent company town set a precedent for creating liveable spaces for workers in isolated locales, influencing later developments. Research included on-site investigations, archival work at Iberdrola's Historical Archive, and review of historical texts, underscoring the cultural and landscape significance of 20th-century dam settlements and the distinctive features of Ricobayo's surroundings.